Novel roles for mucin 1 in the kidney. Issue 5 (September 2017) - Al-bataineh, Mohammad M.; Sutton, Timothy A.; Hughey, Rebecca P.
Abstract : Purpose of review: Recent studies in the kidney have revealed that the well characterized tumor antigen mucin 1 (MUC1/Muc1) also has numerous functions in the normal and injured kidney. Recent findings: Mucin 1 is a transmembrane mucin with a robust glycan-dependent apical targeting signal and efficient recycling from endosomes. It was recently reported that the TRPV5 calcium channel is stabilized on the cell surface by galectin-dependent cross-linking to mucin 1, providing a novel mechanism for regulation of ion channels and normal electrolyte balance. Our recent studies in mice show that Muc 1 is induced after ischemia, stabilizing hypoxia-inducible factor 1 (HIF-1)α and β-catenin levels, and transactivating the HIF-1 and β-catenin protective pathways. However, prolonged induction of either pathway in the injured kidney can proceed from apparent full recovery to chronic kidney disease. A very recent report indicates that aberrant activation of mucin 1 signaling after ischemic injury in mice and humans is associated with development of chronic kidney disease and fibrosis. A frameshift mutation in MUC1 was recently identified as the genetic lesion causing medullary cystic kidney disease type 1, now appropriately renamed MUC1 Kidney Disease. Summary: Studies of mucin 1 in the kidney now reveal significant functions for the extracellular mucin-like domain and signaling through the cytoplasmic tail.